'It was natural and real-life': book clubs as professional development for preservice teachers. Issue 1 (1st January 2023) - Broemmel, Amy D.; Rigell, Amanda; Jordan, Jennifer J.; Rearden, Kristin T.
ABSTRACT: Decades of research indicate teacher dissatisfaction with traditional professional development (PD), while a growing body of research literature indicates the value of heutagogical and andragogical learning in PD. This case study examines the experiences of 43 preservice teachers as they took part in professional development book clubs as part of regular coursework in their educator preparation program. The participants' communities of practice were established across varied platforms: face-to-face meetings, social media groups, and the university learning management system. Participants also collaborated with novel peers from heterogeneous cohorts. Survey data was collected and analyzed to better understand participants' perceptions of the usefulness of the book club PD. Findings include preservice teachers' evaluation of the both the value and format of book clubs as a professional development tool. Implications include suggestions for meaningful collaboration in virtual settings.